GLOBALISASI & IDENTITAS NASIONAL: KONFIGURASI STANDAR HALAL INTERNASIONAL & NASIONAL DI DUNIA ISLAM DALAM TINJAUAN RELASIONAL-INTERSUBJEKTIF: CONFIGURATION OF INTERNATIONAL & NATIONAL HALAL STANDARDS IN THE ISLAMIC WORLD IN RELATIONAL-INTERSUBJECTIVE APPROACH - Moh. Fathoni Hakim (Jisiera: The Journal of Islamic Studies and International Relations, 2023)
Discussions about international halal standards, to this day there is no global halal concept that is universally used. In the Islamic world itself, member countries of the OIC (Organization of Islamic Cooperation) initiated the international halal standard SMIIC (The Standards and Metrology Institute for Islamic Countries) since 2010. But to this day, when OIC member countries conduct international halal trade with other countries members, still use the national halal standards. There is competition between international halal standardization and national halal standards. Or it can also be said that globalization and national identity are fighting, competing for influence in the interpretation of the halal concept. By using a relational-intersubjective approach, this study maps the relationship between the subject “I” and the reality of “phenomen” in viewing international halal standards. Humans will definitely look for meaning in their reality. This framework of thinking is then developed into an intersubjective relation model which requires the relationship between subjects in understanding reality. Reality should not be understood monotonically by one particular subject, but there must be communicative action between subjects in building reality together. International halal standards cannot be monopolized by the interests of certain subjects. There must be communication between subjects to provide a compromise space in formulating international halal standards. This is where globalization and national identity dialogue make compromises in a balanced way.